Long-Term Ringing Data on Migrating Passerines Reveal Overall Avian Decline in Europe - Tina Petras; Al Vrezec (Diversity, 2022)
The loss of biodiversity is shaping today’s environment. Bird ringing is a citizen science research tool that can determine species population dynamics and trends over a large geographic area. We used a 17-year time series to assess population trends of 74 passerine species based on ringing data from autumn migration in Slovenia (south-central Europe). We defined seven guilds of species according to geographic location, ecological, migratory, breeding, and life-history traits. Almost all guilds showed declining trends, except for the group of species of northeastern European origin, which showed a stable trend. The greatest decline was in low-productivity wetland specialists. Forest birds, seed-eaters, and high-productivity species experienced the smallest declines. The general declines in avifauna across a range of life-history and behavioural traits, and across a range of spatial and ecological scales, suggest widespread environmental change in Europe. Our data indicates that recent trends are toward ecosystem homogeneity, with an impoverished avifauna, including a few species that are increasing in abundance. These are the species with higher productivity and flexible behaviour, such as short-distance migrants, that have the greatest chance of prevailing in the recently rapidly changing environment because of their ability to adapt to changes in a timely manner.